1-ethyl-3-(6-methylphenanthridine-8-il) urea modulates TLR3/9 activation and induces selective pro-inflammatory cytokine expression in vitro. Issue 7 (1st April 2017) - Teofilović, Natalija Knežević; Bihi, Mahjoub; Stojković, Marijana Radić; Tumir, Lidija M.; Ester, Katja; Kralj, Marijeta; Majhen, Dragomira; Oršolić, Nada; Lepur, Adriana; Vrbanec, Damir; Markotić, Alemka; Dembić, Zlatko; et al.
Graphical abstract: Abstract: We have previously demonstrated the nucleic acid binding capacity of phenanthridine derivatives (PHTs). Because nucleic acids are potent inducers of innate immune response through Toll-like receptors (TLRs), and because PTHs bear a structural resemblance to commonly used synthetic ligands for TLR7/8, we hypothesized that PHTs could modulate/activate immune response. We found that compound M199 induces secretion of IL-6, IL-8 and TNFα in human PBMCs and inhibits TLR3/9 activation in different cellular systems (PBMCs, HEK293 and THP-1 cell lines).